Trajectories of rice-farming households in mainland Southeast Asia - Cramb, R.A.; Newby, Jonathan Craig (Australian Centre for International Agricultural Research, 2015)
The preceding chapter has demonstrated at the macro-level the importance of agricultural and economic growth for the significant reduction in rural poverty in MSEA that has occurred in recent decades. In this chapter we aim to identify and explain the major trends and trajectories of rice-farming households in the region within this macroeconomic context. We also present a typology of rice-farming households that takes account of the dynamic and diverse nature of rice-based farming systems. These household types and trajectories encompass and help to explain the specific changes in cropping and livestock systems reviewed in Chapters 4, 5, and 6.